2000
DOI: 10.1159/000022959
|View full text |Cite
|
Sign up to set email alerts
|

Association Tests for Traits with Variable Age at Onset

Abstract: This paper is concerned with testing association between marker genotypes and traits with variable age at onset. Two methods are proposed, one which makes use of both age-at-ascertainment and age-at-onset information, and one which may be applied when only age-at-ascertainment information is available. (Here, by age-at-ascertainment, is meant the subject’s age when presence of onset and age at onset are determined; for subjects who have died or are otherwise censored before ascertainment, the censoring time sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…In the following we motivate this coding by showing that in this case, equation (1) takes on the same form as the score equation of a proportional hazards model with an exponential baseline hazard function (this approach can also be generalised to the Cox proportional hazards model. 11 Score equations should merely be considered a (valid) device for coming up with test statistics, see the Discussion.…”
Section: Simple Strategies For Data Analysismentioning
confidence: 99%
“…In the following we motivate this coding by showing that in this case, equation (1) takes on the same form as the score equation of a proportional hazards model with an exponential baseline hazard function (this approach can also be generalised to the Cox proportional hazards model. 11 Score equations should merely be considered a (valid) device for coming up with test statistics, see the Discussion.…”
Section: Simple Strategies For Data Analysismentioning
confidence: 99%
“…Li and Fan (2000) proposed a linkage disequilibrium-based Cox (LDCox) model for nuclear family data and used a robust Wald's test for association. Mokliatchouk et al (2001) and Shih and Whittemore (2002) developed likelihood-based score statistics to test for association between a disease and a genetic marker. The score statistic can be written as a weighted sum over family members of their observed minus expected genotypes.…”
Section: Survival Analysis Methods For Family-based Association Testsmentioning
confidence: 99%
“…In this context the logrank test compares the rates with which individuals of different genotypes are diagnosed with ADHD. When the Breslow estimator is used, it can be shown that this methodology is equivalent to the proportional hazards approaches of Mokliatchouk et al (2001). When parental genotypes are known the FBAT-logrank is also equivalent to Shih & Whittemore's (2002) method.…”
Section: Family-based Association Test-logrank (Fbat-logrank)mentioning
confidence: 99%